Clinical and genetic characteristics of Nonaka myopathy (GNE-myopathy) in russian patients - E. L. Dadali; I. V. Sharkova; G. E. Rudenskaya; S. S. Nikitin; A. F. Murtazina; O. P. Ryzhkova; A. L. Chukhrova (Нервно-мышечные болезни)
Clinical and genetic characteristics of 9patients with Nonaka myopathy (GNE-myopathy) from Russia are presented. As a result of exom sequencing, 11 different mutations were revealed in the GNE gene, 8 of which were described earlier, and 3 – Сys203Ser, Met263CysfsTer and deletion of the whole gene — were detected for the first time. The peculiarities of clinical manifestation of Russian patients with GNE-myopathy are described.